Does Self-Control Promote Prosocial Behavior? Evidence from a Longitudinal Tracking Study - Jingjing Li; Yanhan Chen; Jiachen Lu; Weidong Li; Shuangju Zhen; Dan Zhang (MDPI AG, 2022)
Although numerous researches have shown that self-control is a significant promoter of prosocial behavior, the mechanism behind this relationship is still unclear. According to the organism-environment interaction model and self-control model, this study researched whether life satisfaction played a mediating role between self-control and adolescents' prosocial behavior and if friendship quality played a moderating role between self-control and prosocial behavior. This study used a longitudinal tracking research (T1&T2; and the interval between T1&T2 is 6 months). A total of 1182 Chinese middle school students participated the survey. They were between 12 and 15 years old (average age: 14.16 years old, SD = 1.29). Results indicated that life satisfaction played a mediating role between self-control and adolescents' prosocial behavior. Furthermore, this direct relationship in the link between self-control and prosocial behavior was significant when adolescents had a good-quality friendship. These results highlight that life satisfaction plays an important role in the relationship between self-control and prosocial behavior. The present study further determined that a high-quality friendship was an important factor that amplified this direct effect.